TEACHING CLASSICAL LITERATURE: A SYNTHESIS OF TRADITION AND ORIGINALITY - Intizor Atabekovna Jumaniyazova (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, it is emphasized that such aspects as the teaching of literary science, the past, reading the source step by step in the course of the lesson, listening and paying attention to the written literacy of students are used in the education of madrasahs. . raised In addition, teaching literature in madrasa education, learning complex texts and sources, necessary methods for improvement, showing common methods of modern teaching methods: